Socially responsible investment: a comparison between the performance of sustainable and traditional stock indexes - Curto, J. D.; Vital, C. (Journal of Reviews on Global Economics, 2014)
The doubt about whether socially responsible investment is a viable strategy for investors seeking to maximize both social and financial returns is the central question of this paper. This is addressed by investigating whether portfolio selection based on sustainability criteria harms investor’s returns, or in contrast it can be a driver of superior financial benefits. With this purpose, daily prices and returns of 4 traditional and 10 sustainable stock indexes are analyzed from 2001 to 2011 and in the peaks and downs of both bull and bear markets. One of the major results of this study is that sustainable indexes outperform traditional stock indexes in all the periods under analysis; however the differences on average returns are not statistically significant. Through unit root tests we acknowledge that returns are stationary and levels are nonstationary. The short-run relationship analysis based on Granger causality test reveals a feedback effect between traditional and sustainable stock indexes returns. In contrast, long-run relationship, based on cointegration analysis, points that most of the stock indexes are not cointegrated, suggesting that sustainable and traditional stock indexes do not have a long-run linkage and thus can diverge without bound.